ANALISIS HUKUM PIDANA TERHADAP TINDAK PIDANA KEKERASAN YANG MENGAKIBATKAN KORBAN MENINGGAL DUNIA - Ganda Rona Barus (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
ABSTRACT Hardness doing an injustice can cause its death [of] someone arranged and menaced [by] crime in Assertion of Kesatu Primair impinge Section 170 sentence (2) third KUHP. Problem of this thesis [is] what are the factors that cause violent crimes that result in death of the victim, How is the analysis of criminal law against violent crime whose victims died in the decision of the Medan District Court Number 2462 / Pid.B / 2017 / PN.Mdn.This Research use descriptive method [pass/through] approach of normatif ( legal [of] research) that is approach to problems, [done/conducted] with studying various aspect punish from regulations facet going into effect. Result of research show factors that caused the occurrence of violent crime which resulted in the death of the victim in the Medan District Court decision Number 2462 / Pid.B / 2017 / PN.Mdn was caused by the victim was considered as a police informant so that the defendant became emotional and angry so that the defendant was together- the same as his friends persecuting victims resulting in death based on visum et repertum which explains that the victim died due to heavy bleeding in the head cavity and swelling of the brain due to forced blunt force on the head. Analysis of criminal law against violent crime whose victims died in the decision of Medan District Court Number 2462 / Pid.B / 2017 / PN.Mdn is the application of material criminal law in accordance with the indictment of the Public Prosecutor, namely Article 170 paragraph (2) 3rd Criminal Code. This can be seen from the fulfillment of all elements in accordance with the article imposed by the defendants, namely Article 170 paragraph (2) of the Criminal Code concerning blatant crimes and joint force to commit violence resulting in the death of others and the fulfillment of these elements. and there is no justification and excuse for forgiveness, so the defendants must take responsibility for the actions in accordance with the decision handed down by the Panel of Judges, by serving 7 (seven) years in prison. Judges' considerations in issuing decisions are mitigating that the defendant has acknowledged and regretted his actions, being polite in court, has never been convicted, is still young so that he is expected to be able to improve his behavior in the future and the aggravating thing is the actions of the defendant who play a judge himself troubling the community. Keyword.: Doing An Injustice, Hardness, Death. ABSTRAK Tindak pidana kekerasan dapat menyebabkan matinya seseorang diatur dan diancam pidana dalam Dakwaan Kesatu Primair melanggar Pasal 170 ayat (2) ke-3 KUHP. Permasalahan dalam tesis ini adalah faktor-faktor apakah yang menyebabkan terjadinya tindak pidana kekerasan yang mengakibatkan kematian, bagaimana faktor-faktor yang menyebabkan terjadinya tindak pidana kekerasan yang mengakibatkan korban meninggal dunia, bagaimanakah analisis hukum pidana terhadap tindak pidana kekerasan yang korbannya meninggal dunia pada putusan Pengadilan Negeri Medan Nomor 2462/Pid.B/ 2017/PN.MdnPenelitian ini menggunakan metode deskriptif melalui pendekatan normatif (legal research) yaitu pendekatan terhadap permasalahan, dilakukan dengan mengkaji berbagai aspek hukum dari segi peraturan-peraturan yang berlaku.Hasil penelitian menunjukkan faktor-faktor yang menyebabkan terjadinya tindak pidana kekerasan yang mengakibatkan korban meninggal dunia dalam putusan Pengadilan Negeri Medan Nomor 2462/Pid.B/ 2017/PN.Mdn adalah disebabkan korban dianggap sebagai informan Polisi sehingga terdakwa menjadi emosi dan marah sehingga terdakwa bersama-sama dengan teman-temannya menganiaya korban yang mengakibatkan korban meninggal dunia. Analisis hukum pidana terhadap tindak pidana kekerasan yang korbannya meninggal dunia pada putusan Pengadilan Negeri Medan Nomor 2462/Pid.B/ 2017/PN.Mdn adalah penerapan pidana hukum materiil telah sesuai dengan dakwaan dari Jaksa Penuntut Umum yakni Pasal 170 ayat (2) ke 3 KUHP. Hal ini terlihat atas terpenuhinya semua unsur-unsur sesuai dengan pasal yang dikenakan para terdakwa yaitu Pasal 170 ayat (2) ke 3 KUHP tentang tindak pidana secara terang-terangan dan dengan tenaga bersama melakukan kekerasan yang mengakibatkan matinya orang lain dan terpenuhinya unsur-unsur tersebut dan tidak ada alasan pembenar dan alasan pemaaf sehingga para terdakwa harus mempertanggungjawabkan perbuatan sesuai dengan putusan yang dijatuhkan oleh Majelis Hakim, dengan menjalani pidana penjara selama 7 (tujuh) tahun. Kata Kunci: Tindak Pidana, Kekerasan, Kematian.